The Effect of Mudharabah and Musyarakah Financing on Profitability through Financing t o Deposit Ratio (FDR) as an Intervening Variable in Sharia Commercial Banks in Indonesia - Wartoyo, Wartoyo; Nur Fithriya, Milla; Saefulloh, Eef (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
This research points is to reply questions such as those related to the title Impacts of Mudharabah and Musyarakah Financing on Productivity through Financing to Deposit Proportion (FDR) as an Interceding Variable in Islamic Commercial Banks in Indonesia for the 2018-2022 period. Benefit is measured utilizing Return on Equity (ROE). This investigates strategy employments a quantitative strategy utilizing auxiliary information gotten from the site of the Otoritas Jasa Kesuangan (OJK) for the yearly reports of Islamic Commercial Banks for 2018–2023, information collected by implies of documentation and writing inquire about. The information investigation procedure utilized is way examination utilizing SmartPLS program. The comes about of this think about are: (1) Mudharabah Financing has no impact on Benefit (2) Musyarakah financing contains a significant impact on productivity (3) Mudharabah financing contains a noteworthy impact on FDR; (4) Musyarakah financing has no impact on FDR (5) FDR has no impact on Productivity; (6) FDR cannot mediate the impact between Mudharabah Financing variables on Benefit in Islamic Commercial Banks; (7) FDR cannot intervene the impact between Musyarakah Financing variable Productivity in Islamic Commercial Banks.